The Correlation Between Reading Comprehension Ability and Vocabulary Class IX At SMP N 6 Jambi - Kartika Dewi (Jurnal Sains Sosio Humaniora, 2019)
The main purpose of this study was to find out whether there is any correlation between Reading Comprehension and vocabulary class IX at SMP N 6 Jambi. The hypotheses of this study are, (1) there is no correlation between reading comprehension and vocabulary (2) there is any correlation between vocabulary mastery and reading comprehension. The problem of this research study was: is there any correlation between reading comprehension and vocabulary class IX at SMP N 6 Jambi? The population of this research was 373 students. The sample of this research was 76 students which were taken cluster random sampling from two classes. To conduct this study, qualitative method was used. The data were analyzed by using, Pearson Moment Product Bivariate with SPSS. Based on the findingit was found that the average score reading comprehension test was 56, 5 and the score vocabulary test was 52, 9 .it means that the students' reading comprehension was fair. And the students' competency in vocabulary was fair. Based on the finding, it was found that the correlation coefficient obtained is 0.001. It shows that there is no correlation between vocabulary mastery and reading comprehension and vocabulary.